Partial purification and characterization of cytidine 5'-diphosphate-diglyceride hydrolase from membranes of Escherichia coli. - Raetz, C R (1976)
Cytidine 5'-diphosphate (CDP)-diglyceride is hydrolyzed to phosphatidic acid and cytidine 5'-monophosphate by a specific membrane-bound enzyme in cell-free extracts of Escherichia coli. The hydrolase can be extracted from the particulate fraction with Triton X-100 and purified 1,000-fold in the presence of this detergent. Several nucleoside disphosphate diglycerides were synthesized to determine the substrate specificity of the hydrolase. CDP-diglyceride was hydrolyzed preferentially, although uridine 5'-diphosphate-diglyceride, guanosine 5'-diphosphate-diglyceride, and adenosine 5'-diphosphate (ADP)-diglyceride were also slowly hydrolyzed. Surprisingly, the purified enzyme did not catalyze detectable cleavage of deoxy-CDP (dCDP)-diglyceride. The liponucleotide pool of E. coli contains dCDP-diglyceride and CDP-diglyceride in approximately equal amounts (Raetz and Kennedy, 1973). Water-soluble nucleoside pyrophosphates, such as CDP-choline, nicotinamide adenine dinucleotide, or adenosine 5'-triphosphate are not attacked by this specific hydrolase. Hydrolysis of CDP-diglyceride is strongly inhibited by adenosine 5'-monophosphate and by ADP-diglyceride.